ANALISIS MANAJEMEN RISIKO KEBOCORAN DATA DAN SERANGAN SIBER PADA BPJS KESEHATAN MENGGUNAKAN NIST RISK MANAGEMENT FRAMEWORK : STUDI LITERATUR - ADAM, ALFRINO PATRIANDO (Integrative Perspectives of Social and Science Journal, 2026)
The data breach of BPJS Kesehatan in 2021 became one of the largest cybersecurity incidents in Indonesia, involving millions of citizens’ personal data. This study aims to analyze risk management related to data breaches and cyberattacks using the NIST Risk Management Framework (RMF) approach. The method employed is a literature study with a qualitative descriptive approach by collecting data from scientific journals, regulations, and other credible sources. The results indicate that data breaches are influenced by weak access control, low cybersecurity awareness, and the suboptimal implementation of information security standards. Through the NIST RMF framework, the processes of risk identification, analysis, and control can be carried out more systematically. Therefore, the implementation of this framework is expected to enhance data protection and reduce the risk of future data breaches.